2013
DOI: 10.1111/imm.12173
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for suppressor of cytokine signalling 3 in promoting M1 macrophage activation and function in vitro and in vivo

Abstract: SummaryMacrophages respond to their microenvironment and develop polarized functions critical for orchestrating appropriate inflammatory responses. Classical (M1) activation eliminates pathogens while alternative (M2) activation promotes regulation and repair. M1 macrophage activation is strongly associated with suppressor of cytokine signalling 3 (SOCS3) expression in vitro, but the functional consequences of this are unclear and the role of SOCS3 in M1-macrophage polarization in vivo remains controversial. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(151 citation statements)
references
References 52 publications
9
135
0
7
Order By: Relevance
“…SOCS1 and SOCS3 are most widely characterized regarding their roles in shaping M1 and M2 macrophage polarization (46). They show low expression in resting macrophages, but are rapidly induced on activation.…”
Section: Socs Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…SOCS1 and SOCS3 are most widely characterized regarding their roles in shaping M1 and M2 macrophage polarization (46). They show low expression in resting macrophages, but are rapidly induced on activation.…”
Section: Socs Proteinsmentioning
confidence: 99%
“…Since SOCS3 blocks PI3K that feeds and inhibits TLR responses, this could be an alternative mechanism by which SOCS3 augments TLR signaling in M1 macrophages (6). Forced activation of Notch signaling enhances both M1 polarization and anti-tumor activity via SOCS3 induction (12).…”
Section: Socs Proteinsmentioning
confidence: 99%
“…SOCS3 is a negative feedback regulator of the JAK/STAT signaling pathway [18], which has been indicated to regulate polarization of M1 and M2 macrophages [1921]. TargetScan predicted the 3′ UTR of SOCS3 was potentially targeted by miR-222-3p.…”
Section: Introductionmentioning
confidence: 99%
“…SOCS3 regulates development of M1 cells (42)(43)(44), and SOCS1 regulates polarization to the M2 phenotype (45). Furthermore, overexpression studies in HEK293 and Fao cells have suggested that both SOCS1 and SOCS3 can negatively regulate IRS-2 signaling following insulin stimulation (46,47).…”
mentioning
confidence: 99%